Functional Sub-Circuits of the Olfactory System Viewed from the Olfactory Bulb and the Olfactory Tubercle - Yamaguchi, Masahiro (Frontiers in Neuroanatomy, 2017)
Understanding of the olfactory neural circuits has progressed beyond analysis of how odor information from the external environment is processed in the brain. While spatially-organized sub-circuits were found to exist up to the olfactory bulb (OB), the arrangement in the olfactory cortex (OC), especially in its representative piriform cortex (PC), appears diffuse and dispersed. An emerging view is that the activity of OC neurons may not simply encode odor identity but rather encode plastic odor information such as odor value. Although many studies support this notion, odor value can be either positive or negative, and the existence of sub-circuits corresponding to individual value types is not well explored. To address this question, I introduce here two olfactory areas other than the PC, OB and olfactory tubercle (OT) whose analysis may facilitate understanding of functional sub-circuits related to different odor values. Peripheral and centrifugal inputs to the OB are considered to relate to odor identity and odor value, respectively, and centrifugal inputs to the OB potentially represent different odor values during different behavioral periods. The OT has spatially-segregated functional domains related to distinct motivated and hedonic behaviors. Thus, the OT provides a good starting point from which functional sub-circuits across various olfactory regions can be traced. Further analysis across wide areas of the olfactory system will likely reveal the functional sub-circuits that link odor identity with distinct odor values and direct distinct odor-induced motivated and hedonic behaviors.